14-3-3 Sigma And p53 Expression in Gastric Cancer and Its Clinical Applications. Issue 1 (29th May 2013) - Mühlmann, Gilbert; Öfner, Dietmar; Zitt, Matthias; Müller, Hannes M.; Maier, Hans; Moser, Patrizia; Schmid, Kurt W.; Zitt, Marion; Amberger, Albert
Abstract : 14-3-3 sigma (σ) induces G2 arrest enabling the repair of damaged DNA. The function of 14-3-3 σ is frequently lost in tumor cells, indicating a potential tumor suppressor function. The purpose of this study was to evaluate the prognostic value of 14-3-3 σ expression in human gastric cancer. 14-3-3 σ expression was analyzed by immunohistochemistry in 157 tumor samples of patients, who underwent resection for gastric cancer. Since 14-3-3 σ is involved in the p53 network, p53 expression was detected in parallel and correlated with 14-3-3 σ. 14-3-3 σ was found to be overexpressed in 75 (47.8%) of 157 cases, the overexpression rate of p53 protein was 27.4%. 14-3-3 σ overexpression was statistically significantly associated with pT-stage (p=0.041) pN-stage (p=0.015) and UICC-stage (p=0.019) and showed a borderline significance with Lauren classification (p=0.057). Univariate survival calculations revealed a coexistent 14-3-3 σ and p53 overexpression as a significant predictor of disease-free survival. Multivariate analysis did not unfold 14-3-3 as an independent prognostic factor for disease-free survival and overall survival. Concomitant 14-3-3 σ and p53 overexpression in tumor cells of patients with gastric cancer identifies a population of patients with relatively unfavorable prognosis.